Study On Various Adhesion Mechanism For A Wall Climbing Robot - Yap, Pooi Yee (Universiti Sains Malaysia, 2018)
A wall-climbing robot has provoked high attention worldwide ever since it was born in 1960’s. The main function of a wall-climbing robot to survey human being in highly hazardous and dangerous working environment. The aim of this study is to design and develop adhesion mechanism for a wall climbing robot that is adaptable to the various wall surface. Study of various adhesion mechanism and the design structure on wall climbing robot is required in order to understand the concept and function of a wall climbing robot. The adhesion mechanism used in this wall climbing robot is pushing mechanism with propeller and magnetic attachment system on wheel design to allow the robot stick and move against the vertical wall surface. High torque motor that controlled by the motor-driven which attach with Arduino UNO is used to cover the friction and gravitational force when the robot is moving. With the aid of the Arduino IDE software, the algorithm is built up and the theoretical result is generated to verify the force needed to support the robot move on the vertical wall surface. However, the robot is able to attach on the vertical surface but unable to move against the vertical surface of the ferromagnetic cupboard. The failure analysis is described as power loss and the thrust force generated not strong enough to support the robot move against the vertical surface. Lastly, the concept of adhesion mechanism is work but there is some improvement that can be considered to improve the stability and performance of wall climbing robot.